Heat-Map Algorithm Based Multi-robots Path Planning Method - Bi, Shuhui; Li, Zhihao; Wang, Lei; Xu, Yuan (Multimedia Technology and Enhanced Learning, 2022)
Robot conflicts elimination and efficiency improvement from a global perspective are important issues in intelligent storage systems. In order to improve the operation efficiency of intelligent storage system more effectively, a heat-map Algorithm by combing the reservation table in this paper. Firstly, a small storage grid model applicable to multiple storage modes is established. Secondly, considering the frontal collision problem of multiple robots, an improved reservation table is established, which greatly reduces the storage space occupied and improves the operation efficiency at the same time. In addition, the heat map algorithm is added to reasonably allocate the tasks, avoid the congested area and realize the dynamic assignment of tasks. Finally, the effectiveness of the proposed design scheme is demonstrated by simulation.